iOS implementation of two windowed fourier transform based algorithms for fringe pattern analysis - Zeng, Feifan (2015)
Fringe pattern analysis is the process to extract desired information from a fringe pattern. 2-D windowed Fourier transform is applied to derive the information in this project. Two algorithms, windowed Fourier filtering (WFF) algorithm based on filtering and windowed Fourier ridges (WFR) algorithm based on best matching, were proposed later and also had been demonstrated versatile and effective for fringe pattern analysis. With the rapid development of mobile technology, mobile phones are becoming more and more popular and powerful, especially in image processing area. The implementation of two WFT based algorithms on a mobile platform is of interest. iPhone is chosen as the mobile platform and an iOS application is developed in this project to demonstrate the feasibility. The application analysis, design and implementation are presented with details. The performance of the application is compared with related MATLAB program on PC. Various fringe pattern are used as inputs, the reliability and efficiency is discussed. Some future works are recommended at the end of the report.